Pengembangan Bahan Ajar Geometri SD Berbasis Jajanan Pasar - Damayanti, Alfiana; Sukmawarti, Sukmawarti (Indonesian Research Journal on Education, 2023)
This study aims to find out how effective elementary school geometry teaching materials are based on market snacks and to find out whether these teaching materials can make children like math lessons and get grades according to the criteria. This study uses ADDIE development model which has three stages, namely: (1)Analysis (analysis), (2) Design (design), and (3) Development (development), implementation (implementation), evaluation (evaluation). This development procedure is adjusted to the guidelines for developing teaching materials so that at this stage it consists of several processes. Collecting data in this study using questionnaires and practice questions. Based on the analysis of the data obtained through the validation process carried out by media experts, material experts and teacher responses. The results of the validation test by media experts got a score of "3.8" in the "Good" category, for material experts got a score of "3.75" in the"Good" category and for the teacher's response got a score of "3.75" with the "Good" category. So, it can be calculated that the average score obtained is "3.76" with the "Good" category. Inaccordance with the obtained validation results, it can be concluded that the SD Geometry teachingmaterials based on Snacks Market are feasible to use.